2014
DOI: 10.1074/jbc.m114.590216
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Saccharomyces cerevisiae Tpa1 Protein in Direct Alkylation Repair

Abstract: Background: Fe(II)/2-oxoglutarate (2OG)-dependent dioxygenases repair alkyl-base lesions of DNA. Results: Tpa1 is a Fe(II)/2OG-dependent dioxygenase and mediates alkyl-base repair in Saccharomyces cerevisiae, and deleting TPA1 with DNA glycosylase MAG1 had a synergistic effect on the susceptibility to methylation-induced toxicity. Conclusion: Tpa1 protein plays a crucial role in DNA alkylation repair. Significance: Our results provide the first evidence of direct alkylation repair by any Fe(II)/2OG-dependent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…2). This led us to question the proposed direct participation of Tpa1 in repair of alkylated DNA (7) and to hypothesize that Mag1 may play a larger role in this process than has been appreciated. We showed that Mag1 excises alkylated bases present in duplex DNA that are known to be substrates of the DRR enzyme AlkB, including 3mC and 1mA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This led us to question the proposed direct participation of Tpa1 in repair of alkylated DNA (7) and to hypothesize that Mag1 may play a larger role in this process than has been appreciated. We showed that Mag1 excises alkylated bases present in duplex DNA that are known to be substrates of the DRR enzyme AlkB, including 3mC and 1mA.…”
Section: Discussionmentioning
confidence: 99%
“…S. cerevisiae also expresses Tpa1, which, like E. coli AlkB and many other proteins, is a member of the Fe(II)- and 2OG-dependent dioxygenase superfamily (6). Tpa1 has recently been reported to be a functional homolog of AlkB, acting as an oxidative dealkylase to repair alkylated DNA (7). However, Tpa1 is more closely related to Fe(II)/2OG-dependent dioxygenases that catalyze post-translational hydroxylation of proteins (810), and it has been reported to catalyze prolyl hydroxylation of ribosomal protein S23 and to regulate translation (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…DNA repair was assayed by measuring formaldehyde release as result of removal of methyl-adducts. Formaldehyde was detected by adding acetoacetanilide and ammonia directly to the reaction mix to form fluorescent compound with peak emission of 465 nm ( 27 ) (Supplementary Figure S1A). Concentration of released formaldehyde was determined from the formaldehyde standard curve (Supplementary Figure S1B and C).…”
Section: Resultsmentioning
confidence: 99%
“…[25] Random mutations can also be used to give information on the effect of changing various residues in the active site. [26] An excellent example of directed evolution is the mutation of a transaminase for the asymmetric reduction step in the synthesis of Sitagliptin 16 (Scheme 10). Sitagliptin 16 (marketed as Januvia) is an antidiabetic drug developed and marketed by Merck & Co.…”
Section: Biotechnology: Metagenomics Directed Evolution and Rationalmentioning
confidence: 99%